The Effect of Transfer Pricing, Capital Intensity on Tax Avoidance with Sustainability Report as a Moderation Variable - Cahyani, Anggi Regita; Harnovinsah, Harnovinsah; Darmansyah, Darmansyah; Ambarwati, Sri; Djaddang, Syahril (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Tax data shows an increasing trend in Tax avoidance, with tax target achievements of 107.15% in 2021, 115.6% in 2022, 108.8% in 2023, and 97.2% in 2024, highlighting the need to analyze factors that influence Tax avoidance. On the other hand, sustainability reporting is considered to reflect a company's commitment to transparency and social responsibility, which can reduce the tendency for Tax avoidance. This study aims to examine the effect of Transfer pricing and Capital intensity on Tax avoidance, as well as to test sustainability reporting as a moderating variable. Secondary data were collected from the financial statements and sustainability reports of 20 energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period, with the sample selected using purposive sampling. Analysis was conducted using Moderated Regression Analysis (MRA) via SPSS. The results indicate that before moderation, Transfer pricing has a significant positive effect on Tax avoidance, but after being moderated by sustainability reporting, the effect becomes significantly negative, suggesting that sustainability reporting can curb Tax avoidance practices. Capital intensity has a significant negative effect on Tax avoidance, both before and after moderation. The interactions between Transfer pricing and Sustainability reporting, as well as between Capital intensity and Sustainability reporting, strengthen the influence of the independent variables on Tax avoidance. These findings confirm that sustainability reporting plays a strategic role in enhancing corporate transparency and accountability regarding tax obligations.